Should we perform routine psa testing in all patients over 50 years of age? - Carbone Zárate, Alejandro (Revista del Hospital Italiano de Buenos Aires, 2018)
A healthy 55-year-old man with no family history of prostate disease and no urinary symptoms comes to the clinic for a routine check-up and blood tests. Should we perform routine PSA testing in all patients over 50 years of age?